Effects of vitamin D supplementation on glycated haemoglobin and fasting glucose levels in hypertensive patients: a randomized controlled trial - Grübler, Martin R.; März, Winfried (Diabetes, obesity and metabolism, 2016)
Aim To investigate the efficacy of vitamin D supplementation on glycaemic control. Methods The Styrian Vitamin D Hypertension Trial was a single-centre, double-blind, placebo-controlled study conducted between 2011 and 2014 at the Medical University of Graz, Austria. We enrolled 200 people with arterial hypertension and 25-hydroxyvitamin D [25(OH)D] concentrations <30 ng/mL. Study participants were randomized to receive either 2800 IU of vitamin D or placebo per day for 8 weeks. The present study was a post hoc analysis that incorporated an analysis of covariance (ancova) approach, while adjusting for baseline differences. Results A total of 185 participants [mean ± standard deviation age, 60.1 ± 11.3 years; 47% women; mean 25(OH)D 21.2 ± 5.6 ng/mL, mean glycated haemoglobin (HbA1c) 44.8 ± 11.8 mmol/mol and mean body mass index 30.4 ± 5.4 kg/m2] completed the trial. ancova showed a mean treatment effect [95% confidence interval (CI)] on HbA1c of −3.52 (−6.7 to −0.34) mmol/mol (p = .045). There was no difference in fasting glucose −4.7 mg/dL (95% CI −16.3 to 6.9; p = .426). Conclusions Vitamin D supplementation in obese hypertensive patients with low 25(OH)D reduces HbA1c levels. This finding warrants further investigation into potential vitamin D effects on glucose homeostasis.
Gesehen am 09.07.2019